Equilibrium kinetics and isotherm studies of CU (II) adsorption from waste water onto alkali activated oil palm ash - Chowdhury, Z.Z.; Ahmed, A.A.; Khan, R.A.; Zain, Sharifuddin Md (2011)
Problem statement: Heavy metal accumulation in waste water could affect aquatic life, human health and overall ecosystem adversely. Therefore, in recent years much emphasis has been given for the use of industrial waste material as low cost adsorbents for removal of metallic contaminants from waste water. Approach: Present study deals with the adsorption equilibrium and kinetics of Cu (II) cation using sodium hydroxide activated Oil Palm Ash (OPA). Adsorption was investigated in a batch system with respect to various parameters such as initial metal ion concentration, contact time and pH of the solution. Surface characterization of the prepared adsorbent was done by using surface area analyzer, Scanning Electron Microscope (SEM) and X-ray Fluorescence and compared with natural oil palm ash. The adsorption equilibrium data were best represented by Langmuir, Freundlich and Temkin model. Equilibrium kinetics studies were performed by Pseudo first order, Pseudo second order and Intra-particle diffusion. Results: Maximum monolayer adsorption capacity observed at 30°C was 18.86 mg g -1. Kinetic data correlated well with the pseudo second order model, suggesting that the adsorption process might be chemical sorption. The linear plots of intra particle diffusion revealed that the adsorption process was mainly governed by pore diffusion. Equilibrium uptake was increased with increase of initial concentration and contact time. Experimental data showed that about 96.03% of copper can be removed at pH 5.5. Conclusion: The research concluded that activation by alkali treatment of natural OPA would produce sufficient porosities and surface area and it has got good potential to remove Cu (II) from waste water. © 2010 Science Publications.